The promise of targeting heme and mitochondrial respiration in normalizing tumor microenvironment and potentiating immunotherapy - Akter, Zakia; Salamat, Narges; Ali, Md. Yousuf; Zhang, Li (Frontiers in Oncology, 2023)
Cancer immunotherapy shows durable treatment responses and therapeutic benefits compared to other cancer treatment modalities, but many cancer patients display primary and acquired resistance to immunotherapeutics. Immunosuppressive tumor microenvironment (TME) is a major barrier to cancer immunotherapy. Notably, cancer cells depend on high mitochondrial bioenergetics accompanied with the supply of heme for their growth, proliferation, progression, and metastasis. This excessive mitochondrial respiration increases tumor cells oxygen consumption, which triggers hypoxia and irregular blood vessels formation in various regions of TME, resulting in an immunosuppressive TME, evasion of anti-tumor immunity, and resistance to immunotherapeutic agents. In this review, we discuss the role of heme, heme catabolism, and mitochondrial respiration on mediating immunosuppressive TME by promoting hypoxia, angiogenesis, and leaky tumor vasculature. Moreover, we discuss the therapeutic prospects of targeting heme and mitochondrial respiration in alleviating tumor hypoxia, normalizing tumor vasculature, and TME to restore anti-tumor immunity and resensitize cancer cells to immunotherapy.